2005
DOI: 10.1021/jo050288g
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Polarities of Some Ionic Liquids Using 2-Nitrocyclohexanone as the Probe

Abstract: Solute-solvent interactions on the keto-enol tautomerism of 2-nitrocyclohexanone in several organic solvents and room-temperature ionic liquids (RTILs) have been analyzed in terms of multiparameter equations. Permittivity and cohesive pressure values of the RTILs, unavailable by direct measurements, have been derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 43 publications
3
74
0
1
Order By: Relevance
“…However, one particularly thorough study of polarity using reaction dynamics bears special mention. Angelini et al [40] observed the tautomerization of a nitroketone complex in a series of five imidazolium-based ionic liquids, and conducted a linear free energy analysis of the behavior of the equilibrium constant. The results indicate an overall polarity comparable to that of acetonitrile, and the details of the linear free energy relationship analysis seem consistent with the partitioning and spectroscopic studies above.…”
Section: The Chemical Environment Of Ionic Liquidsmentioning
confidence: 99%
“…However, one particularly thorough study of polarity using reaction dynamics bears special mention. Angelini et al [40] observed the tautomerization of a nitroketone complex in a series of five imidazolium-based ionic liquids, and conducted a linear free energy analysis of the behavior of the equilibrium constant. The results indicate an overall polarity comparable to that of acetonitrile, and the details of the linear free energy relationship analysis seem consistent with the partitioning and spectroscopic studies above.…”
Section: The Chemical Environment Of Ionic Liquidsmentioning
confidence: 99%
“…Probe based analysis have included both single parameter studies based on, for example, pyridinium Nphenolate betaine dye, 8,9 nile red 10,11 and 2-85 nitrocycloexanone 12 and multiparameter studies using the Kamlet-Taft parameters 5,[13][14][15] . Solvatochromic methods are based on the fact that these dyes interact with the solvent into which they are added and the extent of these interactions is shift in the energy levels associated with the dye electronic transitions in the visible region and a corresponding shift in the absorbance of the dye 9 .…”
mentioning
confidence: 99%
“…8 The degree of order may also influence solvation and organic reactivity by ordering the reactants. 9,10 In a previous paper, 11 we have shown that the keto−enol interconversion of 2-nitrocyclohexanone (2-NCH) is a suitable probe reaction for investigating the complexity of the effects of RTILs at the molecular level.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11 The tautomeric equilibrium is displaced toward the keto form upon transfer from apolar organic solvents to RTILs as the cavitational and nonspecific electrostatic effects that stabilize the ketone overwhelm the specific electrostatic contributions that stabilize the enol.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation